Investigation on 4THz quantum well photodetector - Zhuang, Zichang (2015)
Band parameters of III-V semiconductor quantum well of AlGaAs/GaAs and InGaAs/Ga has been numerically calculated. Numerical simulation based on Visual Basic software is introduced to analyze the characteristics of band structures and respective band parameters to achieve terahertz (THz) quantum-well photodetector. The analysis and simulation of certain key parameters of quantum well of AlGaAs/GaAs and InGaAs/Ga were achieved. Eight-band k.p method approach has been commonly employed to compute of the band parameters and subband transitions. More critically, certain key parameters like, absorption energy, thickness of the well width and doping concentration have been further analyzed. The simulation of quantum well of AlGaAs/GaAs and InGaAs/Ga have shown that 4THz can be obtained for certain value of well width provided with 300 k temperature by varying the doping concentration and thickness of the well width. The results of AlGaAs/GaAs and InGaAs/Ga material quantum well thickness and respective composition ratio were clearly shown that the two compound semiconductor material can be utilized to generate 4THz from software simulation. The energy levels and absorption of a 4 THz quantum well intersubband transition is demonstrated with GUI (Graphical User Interface) based on the Visual Basic.